Configuration of the lobed nozzle in an ejector mixer for extreme mixing efficiency. (February 2022) - Sheng, Zhi-qiang; Zhang, Lan; Dan, Yu; Wang, You-yuan
Highlights: The jet mixing of lobed nozzles with complex configurations is studied. The mixing in the core region of a lobed nozzle is effectively enhanced. A lobed nozzle configuration with extreme mixing efficiency is obtained. The relationship between the longitudinal vortices and mixing rate is elucidated. Suggestion for designing a lobed nozzle with high mixing efficiency is provided. Abstract: An alternating-lobe nozzle with nail-like crests and sword deep valleys (NSALN-1) was modified to achieve the ultimate mixing efficiency by enhancing the mixing in the core region. The main modifications included extending the sword deep valleys, adding a central plug between the sword deep valleys, and connecting the sword deep valleys to form arched deep valleys. The jet mixing of NSALN-1 and its modified configurations was numerically simulated, and the efficiency of the modifications was investigated. It was found that each modification can improve the thermal mixing efficiency, but also reduce the total pressure recovery coefficient. In particular, adding a central plug of an appropriate size can increase the thermal mixing efficiency to an extreme value while the reduction in the total pressure recovery coefficient remained within an acceptable range. The thermal mixing efficiency can reach 0.98 at 1.5 d and exceed 0.99 at 2.0 d . Furthermore, the shape and position of the longitudinal vortex determine the length of the path by which the cold stream is transported to mix with the hot stream by the longitudinal vortex. Regulating the mixing in each region to achieve balanced mixing speeds is thus helpful to achieve the ultimate mixing efficiency of the circularly lobe nozzle.